Chemistry Related Research at the Institute of Nanoscience and Nanotechnology, NCSR “Demokritos”, Greece - Yannakopoulou, Konstantina; Lazarou, Yannis G.; Gogolides, Evangelos (ChemPlusChem (Weinheim, Germany), 2025)
The Institute of Nanoscience and Nanotechnology (INN) is part of the National Center for Scientific Research “Demokritos” (NCSRD), located in Aghia Paraskevi, Attiki, Greece. The research carried out at INN is multidisciplinary, giving rise to a multitude of research projects in the areas of chemical sciences for nanostructures and biological applications, cultural heritage, magnetism and superconductivity, nanochemistry, as well as nanomaterials, nanoelectronics, photonics, and microsystems. The research activities in INN span the range from fundamental physical sciences and engineering principles to innovative applications in: environment, energy, and industry; digital technology, space, security, and defense; quantum materials and technology; health and agrofood; and culture and climate. In this Institute Feature, a number of articles are presented reporting recent research in which chemistry is an essential component. The Institute of Nanoscience and Nanotechnology (INN), part of the National Center for Scientific Research “Demokritos” (NCSRD) in Greece, is a dynamic Institute with a broad range of research topics. INN fosters multidisciplinary research in Chemistry, Materials, and Microelectronics across contemporary subjects. This Institute Feature contains articles reflecting current chemistry‐related research, and recent articles published in other Wiley‐VCH journals.